Experimental optimisation of the pitching structural parameters of a fully passive flapping foil turbine. (June 2021) - Duarte, Leandro; Dellinger, Nicolas; Dellinger, Guilhem; Ghenaim, Abdellah; Terfous, Abdelali
Abstract: A reduced scale prototype of a fully passive flapping foil turbine has been designed and tested in a confined channel at a chord Reynolds number of 60 000. Thanks to an original dynamic tuning strategy of the mechanical properties, experiments have been conducted in a wide range of pitching structural parameters for three different pitching axis locations. The best performances have been achieved when the pitching axis is located at one third of the chord length, for which a hydraulic efficiency of 31.9% has been reached. Relatively good harvesting metrics have also been obtained while moving the pitching axis back to the trailing edge, as long as the pitching stiffness is increased accordingly. The experimental results showed as well that the energy harvested by the pitching motion is negligible compared with the heaving motion. However, a non-zero pitching viscous damping is required in order for the turbine to achieve its best performances. Highlights: Optimised configuration reaches a hydraulic efficiency of 31.9%. Best performances when the pitching axis is close to one third of the chord length. Some pitching stiffness is needed if the pitching axis is further downstream. Energy harvested from pitching is negligible compared to that from heaving. Non-zero pitching viscous damping enhances energy harvesting from heaving.